Anxiety in Children with Low Vision Secondary to Refractive Errors - Sinan Bekmez; Dilem Eris; Irfan Perente (Beyoglu Eye Journal, 2020)
INTRODUCTION[|]This study aimed to evaluate the anxiety status of children with low vision due to refractive errors using a questionnaire survey.[¤]METHODS[|]Between July and November 2019, the Screen for Child Anxiety Related Emotional Disorders (SCARED) questionnaire was administered to children with refractive errors (≥3D) and amblyopia who presented to the ophthalmology clinic. Children with low vision were evaluated based on their answers to the SCARED questionnaire.[¤]RESULTS[|]This study included 38 children (22 girls, 16 boys) with low vision. The average age of the participants was 9.74+-2.65 (7–12) years. The average binocular vision was 0.28+-0.21 LogMAR. The mean total anxiety score was 21.68+-10.55. At least one type of anxiety was detected in 18 (47.4%) children. A positive correlation and statistical significance were found between binocular low vision and anxiety (r=0.63, p<0.001). Boys were more susceptible to anxiety than girls, and a positive moderate correlation and statistical significance were found (r=0.50, p=0.002).[¤]DISCUSSION AND CONCLUSION[|]Anxiety may develop in children with low vision, and this anxiety more commonly occur in boys than in girls (p=0.002). In addition, psychological disorders can be seen in children with low vision. To better evaluate this connection, large case series studies including visual impairment due to different reasons are needed.[¤]